Peran Intensifikasi dan Ektensifikasi dalam Pengembangan Komoditas Kakao di Wilayah Pesawaran dan Tanggamus - Nadila Nadila; Erlin Kurniati (SUAN PUBLISHER, 2025)
This study explores the roles of intensification and extensification in the development of cocoa commodities in Pesawaran and Tanggamus districts. Intensification involves optimizing agricultural practices to increase cocoa yields per unit area, such as applying modern technologies, improving soil fertility, and adopting effective cultivation techniques. Extensification, on the other hand, focuses on expanding cocoa cultivation areas by utilizing previously unused or underutilized land. The research adopts a qualitative approach through interviews with cocoa farmers, agricultural extension agents, and relevant stakeholders. Secondary data from agricultural statistics and government reports are also analyzed to gain a broader understanding of cocoa development trends. The primary aim is to evaluate how these two strategies intensification and extensification contribute to improving productivity and farmers’ livelihoods. By comparing the outcomes in each region, the study seeks to identify best practices and challenges associated with implementing both approaches. The expected findings will offer insights into sustainable cocoa farming strategies and highlight the potential of cocoa as a key economic crop in these regions. Additionally, the study aims to generate policy recommendations for local governments to support cocoa development in a way that balances productivity, environmental sustainability, and socio-economic advancement.